TGFβ activating integrins β6 and β8 are dysregulated in inflammatory skin disease and cutaneous melanoma. Issue 1 (April 2022) - Nguyen, Breanna A.; Ho, Jonhan; De La Cruz Diaz, Jacinto S.; Nishimura, Stephen; Kaplan, Daniel H.
Highlights: Expression of β6 and β8 in human skin recapitulates expression in murine skin. Skin from inflammatory conditions show increased integrin β6 expression. Compared to benign nevi, melanomas show increased integrin β8 expression. Increased integrin β8 expression may be a prognostic factor in melanoma. Abstract: Background: Integrins avβ6 and avβ8 are expressed by keratinocytes and transactivate latent TGFβ. In a murine model, integrin mediated activation of TGFβ has been shown to be critical in maintaining skin homeostasis, specifically playing roles in epidermal retention of Langerhans cells and resident memory cells T cells (Trm). Objective: We examine expression of Integrins β6 and β8 in human skin, inflammatory skin disease, benign nevi, and melanoma and hypothesize that integrin expression is dysregulated in disease. Methods: Using immunohistochemistry, we stained tissue from normal human skin (n = 8), psoriasis (n = 6), atopic dermatitis (n = 6), lichen planus (n = 5), benign nevi (n = 24), and melanoma (n = 25) with anti-integrin β6 and anti-integrin β8 to survey expression pattern. We also performed a retrospective chart review in the melanoma cohort to examine if integrin β6 and β8 expression was associated with increased Breslow depth and worse prognostic staging. Results: Here, we show that human keratinocytes express integrins β6 and β8, similar to murine keratinocytes. We also found that inflammatory skin conditions have increased Integrin β6, but not Integrin β8 expression. Furthermore, we identified that melanomas have greatly increased expression of integrin β8 compared to nevi. Additionally, high expression of integrin β8 was correlated with greater Breslow depth at diagnosis and with worse prognostic staging. Conclusion: These findings demonstrate that like murine keratinocytes, human keratinocytes express integrin β6 and β8 under steady state conditions. Moreover, altered integrin expression may participate in the development or maintenance of cutaneous inflammation as well as tumor immune evasion.